2003
DOI: 10.1016/s0741-5214(03)00125-3
|View full text |Cite
|
Sign up to set email alerts
|

Transient exposure to elastase induces mouse aortic wall smooth muscle cell production of MCP-1 and RANTES during development of experimental aortic aneurysm

Abstract: Increased mouse aortic wall expression of MCP-1 and RANTES occurs early in development of elastase-induced AAA and before onset of the chronic inflammatory response. Moreover, elastase directly stimulates AoSMC chemokine production in vitro. Elastase-induced medial SMC production of CC chemokines may therefore provide an important link between enzymatic injury, leukocyte recruitment, and aneurysmal degeneration of the aortic wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 40 publications
4
47
1
Order By: Relevance
“…MCP-1 was highly expressed in human AAA samples 10 and experimentally induced AAA model in mice. 27 Its receptor, C-C chemokine receptor 2, plays a crucial role in angiotensin II-induced development of AAA formation in mice. 12 The decreased incidence of early aneurysmal changes in MCP-1 -/-mice strongly suggests that MCP-1 also contributes to the initiation of CA formation.…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 was highly expressed in human AAA samples 10 and experimentally induced AAA model in mice. 27 Its receptor, C-C chemokine receptor 2, plays a crucial role in angiotensin II-induced development of AAA formation in mice. 12 The decreased incidence of early aneurysmal changes in MCP-1 -/-mice strongly suggests that MCP-1 also contributes to the initiation of CA formation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, elastase perfusion enhanced mast cell numbers in the aortas. One possible explanation is that elastase perfusion induces aortic wall SMC expression of chemokines MCP-1 and RANTES (49), which may attract mast cells (50). Further, elastase perfusion may generate elastin degradation products that signal fibroblast, monocyte, and macrophage chemotaxis (51).…”
Section: Discussionmentioning
confidence: 99%
“…RANTES is thought to be released by activated T lymphocytes and monocytes/macrophages, epithelial cells, bronchial epithelium, and dermal fibroblast and renal tubular epithelium. It has been demonstrated that RANTES plays an important role in a variety of disease states, including allergic inflammatory processes such as asthma, allergic rhinitis, and atopic dermatitis (Colonnello et al 2003). Niwa et al (2001) have found that plasma RANTES levels are significantly increased in the patients with severe, treatment-resistant atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%